A prospective randomized single blind study to compare the safety and efficacy of propronolol and topiramate in migraine prophylaxis - Rajkumar, Keelu; Kumar, Pothuru Anil (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The aim of the study was to compare the Safety and efficacy of propranolol and topiramate in migraine prophylaxis. Methods: This was a prospective, randomized, single blind study which was conducted for six months in 100 patients of outpatient department of Neurology Government General Hospital, Guntur. Results: Among the hundred patients fifty were allotted to group A – propranolol 40 mg bd and fifty were allotted to group B- topiramate 25 mg bd. statistically there is no significant differences were found between the treatment groups of Propranolol and topiramate for the reduction in mean duration and severity of migraine headaches. Both Propranolol and topiramate have p value<0.001. This shows that both propranolol and topiramate have significantly decreased in the mean duration and severity of migraine attacks. However, in the present study topiramate is slightly more efficacious in reducing the symptoms of migraine frequency per month (days), duration and severity (visual analogue scale- VAS score) from baseline at the end of six months. The decrease in frequency of migraine attacks from 10.44±4.38 to 3.18±4.48 i.e., 70.2% from baseline is seen with topiramate. Conclusions: This study demonstrated that both propranolol and topiramate could significantly reduce migraine headache frequency, duration and intensity. However, compared with propranolol topiramate showed better results. topiramate 25 mg reduced the symptoms like frequency, duration and severity of migraine attacks from base line at the end of six months but more number of adverse effects were seen in topiramate group.